Validation of a Radio frequency identification system for tracking location of laying hens in a quasi-commercial aviary system - Gebhardt-Henrich, Sabine G.; Kashev, Alexander; Petelle, Matthew B.; Toscano, Michael J. (Peer Community Journal, 2023)

(untitled)
Cage-free housing is increasingly chosen in Europe, North America, and Australia as an animal-welfare friendly farm system for laying hens. However, hens are kept in large numbers in those systems which makes checking for health and welfare difficult and individuals cannot be identified. Tracking systems like radio frequency identification allow researchers to monitor these individuals almost continuously. Individual tracking data has revealed substantial individual variation in movement patterns, however, in recent studies, only a subset of animals per flock was tracked. We applied an RFID tracking system to monitor all 1125 laying hens of a flock, which were divided into 5 pens of 225 birds each in a barn with an aviary system. In each pen, 26 antennas were placed on the edges of three tiers and in the litter. For validation purposes, 3 hens in 2 connected pens were fitted with colored backpacks. They were recorded on video and their location throughout the pen was taken from the video and compared with registrations from the RFID system. For 93% of compared transitions, the RFID data matched the observational data regarding the tier or litter whereas the value fell to 39%  for specific antennae. When the antennae on the litter were excluded for the validation, the match on tier-level was at least 98% but on antenna-level it remained lower than 50%. The sensitivity of the detection of tiers/litter but not antennae differed among the three hens. We conclude that the RFID tracking system was suitable for studying the movement pattern of individual hens among tiers in an aviary system in a reliable way but tracking birds on the litter needs to be improved.